PENINGKATAN KEMAMPUAN MAHASISWA TERHADAP MATA KULIAH KIMIA ORGANIK 1 MELAL UI PEMBELAJARAN DENGAN PENDEKATAN "CHEM0-ENTREPRENEURSHIP" - Titi Wahyukaeni (JURNAL LITBANG PROVINSI JAWA TENGAH, 2007)
The study proces of Organic Chemistry I lecture isn't oriented yet for the life skill. The lecturer doesn't give the opportunity for the students to do scholarly job. So, 50 % students' ability get value under 70, it means that almost a half ofall students have gotten enough capability, even lower. Therefore, it needs applying study with "Chemo-Entrepreneurship" approach to increase the students' ability. Subject of research is the students ofChemistry Education program who's going through the Organic Chemistry I semester 2 of2005/2006. This research uses an action of each rotation consisted of the planning, action implementation, observation and reflection. The result of the research shows that the mean of enlargement value, Good Team at the first rotation, but the students' ability "ere still IO,::!% who got value upper 80. On the second rotation, the mean of enlargement value. Super Great Team, where the students were getting value upper 80 reaching 84, I%. It have fulfilled the expected goals.